2017
DOI: 10.1038/s41467-017-01022-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding of the Tet-transactivator curtails antigen-induced lymphocyte activation in mice

Abstract: The Tet-On/Off system for conditional transgene expression constitutes state-of-the-art technology to study gene function by facilitating inducible expression in a timed and reversible manner. Several studies documented the suitability and versatility of this system to trace lymphocyte fate and to conditionally express oncogenes or silence tumour suppressor genes in vivo. Here, we show that expression of the tetracycline/doxycycline-controlled Tet-transactivator, while tolerated well during development and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…There is increasing evidence that transgenes believed to be inert (e.g., Cre recombinase, GFP, bacterial transactivators) can have significant effects on cell function and viability ( 20 , 21 ). Based on these concerns, we investigated the impact of Tet-Off system components on glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that transgenes believed to be inert (e.g., Cre recombinase, GFP, bacterial transactivators) can have significant effects on cell function and viability ( 20 , 21 ). Based on these concerns, we investigated the impact of Tet-Off system components on glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that common drugs used to control transgene expression can have off-target effects on mitochondrial and metabolic function 28 . Moreover, there is increasing evidence illustrating that overexpression of transgenes previously believed to be inert (e.g Crerecombinase, GFP, transactivator) can have significant effects on cell function and viability 34,35,[41][42][43] . Based on these concerns, we performed a series of in vivo experiments to investigate impact of the Tet-Off system components on glucose metabolism in males and females over time.…”
Section: Mip-itta Mice Are Glucose Intolerant Due To Insufficient Insmentioning
confidence: 99%
“…The improved tTA transactivator (itTA) 32 has been successfully used in combination with the MIP promoter to drive islet transgene expression 33 . However, in light of recent challenges in other models 14,15,31,34,35 , additional studies are required to evaluate the efficiency, specificity, and potential off-target effects of this system for beta cell targeting.…”
Section: Introductionmentioning
confidence: 99%
“…458,459 Tetracycline/doxycycline-inducible Tet-Off/Tet-On system Apoptotic response in activated lymphocytes resulting from DNA binding by tTA/rtTA. 464 Classical reporter molecules Increase in the CTL response against transplanted eGFP-expressing leukemia cells in BALB/c mice; IFNγ response to the dominant CTL epitope of Luc, with consequent restricted growth and metastatic activity of the reporter-labelled tumor cells in a mouse model of mammary adenocarcinoma; antigen specific activation of T cells to the reporter gene β-galactosidase, with loss of transgene expression. 465 The "mild" cold stress caused by standard sub-thermoneutral housing temperatures affects immune responses, tumor growth, and other experimental outcomes.…”
Section: Crispr-cas9mentioning
confidence: 99%
“…These findings indicate that a major experimental bias exists in the use of the Tet-On/Off system for lymphocyte targeting as the approach may (1) limit the extent of the adaptive immune reaction and (2) favor the outgrowth of apoptosis-resistant subpopulations of lymphoid cells. 464 Expression of fluorescent or enzymatic reporters driven by gene-specific regulatory elements is used to study in vivo or ex vivo activity and distribution of specific molecular targets or mutant alleles in GEM models. However, an increasing number of studies show that reporters can be highly immunogenic.…”
Section: Unintended Consequences Of Genetic Engineering Strategiesmentioning
confidence: 99%